Septic arthritis caused by Candida albicans: post intra-articular steroid injection in a native joint - Chung, Siok Li (BMJ Case Rep, 2020)
Intra-articular steroid injections are widely prescribed for management of osteoarthritis when oral medication or physiotherapy treatment fails to relieve patient’s pain. Septic arthritis is an uncommon side effect of steroid injection. Common causal micro-organisms are bacterial with Staphylococcus aureus being the most frequent. Fungal septic arthritis is rare and does not usually present beyond the neonatal period. We present a rare case of septic arthritis secondary to fungal infection.